WEB TOOLS AND TECHNOLOGIES TO INCREASE CITATION FREQUENCY BY USE OF SOCIAL MEDIA: AN APPRAISAL - Khan, Khaisar Muneebulla; Ali, K. S. (International Journal of Research -GRANTHAALAYAH, 2020)
Increasing technological advances and its applications in library and information centres and services have enabled users to access voluminous quality information through Internet. No doubt, World Wide Web (WWW) can be considered as one of the most innovative, magnificent and remarkable service of the 21st century. It has become most popular and convenient to share, publish, communicate and disseminate information instantly among researchers, scientist and academic community. The library profession, researchers and scientist are anonymous to agree that social networks and social media have completely revolutionise the ways and means to access, communicate share, and disseminate nascent thoughts, ideas, and information at much faster pace. This networking of information and communication facilities build rapport, connections and collaborations with peer groups, similar organisations and institutions which in turn promotes academic, research and development. The article provides in brief different networking resources, tools and techniques and the significant role of played by social media on researchers and scientist for academic progress and developments.